Willingness to Communicate from Indonesian Learners’ Perspective: A DYNAMIC COMPLEX SYSTEMS PERSPECTIVE - Eka Fadilah (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2018)
The present study is aimed at investigating dynamic complex systems and sub-systems underlying students’ willingness to communicate (WTC) in the classroom context. The fact that students’ reticence still arises during the classroom discussion until to date. It is insufficient to see students’ willingness to communicate from a single perspective. Seen from dynamic complex theory, the present study postulates the systems and sub-systems underlying students’ willingness to communicate in L2 that are dynamic and interconnected one to another. I conducted a naturalistic inquiry by investigating eight Indonesian university students (4 low English proficiency students and 4 high English proficiency students). A number of research instruments (face to face interview, online interview, and students’ log) were used to collect the data with regard to the students’ participation in the classroom. The finding reveals that classroom systems such as social and classroom context, linguistic competence, individual differences, and cultural context affect participants’ WTC in L2. Those systems encompass some sub-systems interacting and interconnecting one to another that affect classroom communication in second language.